Impact of internet gaming disorder on self-efficacy and self-doubt among university students - Ahsan, Sadaf; Rasheed, Amna; Zonash, Rabia (Pakistan Journal of Physiology, 2019)
Background: Increase in internet gaming disorder among adolescents is causing various psychological problems which leads to different cognitive distortions. The current study was planned to investigate the impact of internet gaming disorder on self-efficacy and self-doubt among university students. Methods: The sample of 300 students was collected through purposive sampling technique, from different universities of Islamabad and Rawalpindi. Self-report measures, i.e., Internet Gaming Disorder Scale-short Form, General Self-Efficacy Scale, and Causal Uncertainty Scale were administered. The data was analyzed through SPSS finding frequencies and using t-test and Regression. Results: Prevalence showed that internet gaming disorder was found to be more in young adults, undergraduate 127 (42.3%), graduate 143 (47.7%), and postgraduate 30 (10.0%). Males reported high levels of internet gaming disorder (23.91±5.14) as compared to females (18.96±5.47). Males showed more self-doubt (46.83±11.36) than females (41.86±10.41), while females showed more self-efficacy (28.77±5.30) than males (27.38±4.84). Conclusion: There is a significant difference between males and females in terms of internet gaming disorder, self-efficacy and self-doubt. Males have more internet gaming disorder and self-doubt than females. Females have more self-efficacy than males. Pak J Physiol 2019;15(4):38?41